Vertebral body stenting / stentoplasty (Swiss Medical Weekly, 2012)
Osteoporotic vertebral fractures are frequent. Although the majority of fractures follow a benign course, there are certain fracture types which result in severe spinal deformity and / or are associated with neurological complications. These patients should be detected early and undergo surgical treatment. Vertebroplasty remains an important and effective treatment option for acute painful vertebral fractures showing progressive collapse. By this procedure the fracture can be stabilised, the pain is controlled and the progression of height loss is also halted. If a vertebral body shows a higher degree of collapse and kyphotic deformity or even some posterior wall involvement, the stentoplasty procedure (further evolution of kyphoplasty) allows height resotartion by the stent and the stabilisation of the vertebral body by cement.